2013
DOI: 10.1186/1824-7288-39-50
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drugs and breastfeeding

Abstract: IntroductionThis review provides a synopsis for clinicians on the use of antiepileptic drugs (AEDs) in the breastfeeding mother.MethodsFor each AED, we collected all retrievable data from Hale’s “Medications and Mother Milk” (2012), from the LactMed database (2013) of the National Library of Medicine, and from a MedLine Search of relevant studies in the past 10 years.ResultsOlder AEDs, such as carbamazepine, valproic acid, phenytoin, phenobarbital, primidone are considered to have a good level of safety during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
31

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 64 publications
2
38
0
31
Order By: Relevance
“…Because three consecutive Finnegan scores averaging 8 or greater, or two scores averaging 12 or greater, did not occur and because the oxcarbazepine concentration of the infant was relatively low, oxcarbazepine was directly discontinued rather than gradually withdrawn from the infant, and no treatment other than supportive care was needed. In terms of feeding, the oxcarbazepine steady‐state peak milk concentration of the mother was 7.8 mg/L, consistent with the 0.5 milk : plasma concentration ratio reported in the literature . HLA‐B*1502 genotype testing of the infant was performed by a pharmacist to evaluate the risk of carbamazepine‐related toxic effects, which revealed that the infant was HLA‐B*1502 negative.…”
Section: Case Reportsupporting
confidence: 87%
“…Because three consecutive Finnegan scores averaging 8 or greater, or two scores averaging 12 or greater, did not occur and because the oxcarbazepine concentration of the infant was relatively low, oxcarbazepine was directly discontinued rather than gradually withdrawn from the infant, and no treatment other than supportive care was needed. In terms of feeding, the oxcarbazepine steady‐state peak milk concentration of the mother was 7.8 mg/L, consistent with the 0.5 milk : plasma concentration ratio reported in the literature . HLA‐B*1502 genotype testing of the infant was performed by a pharmacist to evaluate the risk of carbamazepine‐related toxic effects, which revealed that the infant was HLA‐B*1502 negative.…”
Section: Case Reportsupporting
confidence: 87%
“…In some cases, it also includes checking the infant’s plasma drug levels. (Davanzo, 2013) Bhutanese WWE were most often taking phenytoin which has a low degree of penetration into breast milk, and carbamazepine which has a moderate milk-to-plasma ratio. (Veiby, 2015) AED levels are presently not available for measurement through laboratories in Bhutan.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in utero exposure, in which the fetal levels are similar to maternal plasma concentrations, AEDs are differentially secreted into human milk. Phenytoin and valproate are considered safe due to very low concentrations found in milk (5). By contrast, the levels of levetiracetam in breast milk are high and may be equivalent to a therapeutic dose.…”
Section: Commentarymentioning
confidence: 99%